In silico, In vitro studies of Anti-Oxidant and Anthelminthic Abilities of Phytoconstituents from Rhynchosia cana (Wild.) DC. - Yempada, Praveena; Marrisetti, Arya Lakshmi; Battu, Ganga Rao (Iraqi Journal of Pharmaceutical Sciences, 2022)
Helminthiasis is a significant economic burden on grazing cattle. Increased resistance to currently available synthetic anthelmintics used to treat helminthiasis, and anthelmintic residues in meat and dairy products pose a significant worldwide health threat. These obstacles require the development of new anthelmintics capable of combating drug resistance while also exhibiting improved safety profiles. Rhynchosia cana (Fabaceae) is a herb that has historically been used as a worm expeller. To evaluate the phytochemical profile and explore the anti-oxidant and anthelmintic effects of different extracts of Rhynchosia cana (R. cana) by In silico and In vitro methods. Using standardised chemical tests as defined in the literature, phytochemical research was carried out. Using 2,2-diphenyl-1-picrylhydrazyl (DPPH) and Hydrogen peroxide (H2O2) radicals scavenging assay, In vitro free radical scavenging behaviour of different extracts was quantitatively estimated, whereas In-vitro anthelmintic activity was measured against Pheretima posthuma (P. posthuma) (Annelida). The molecular docking analysis was then carried out to establish compounds with good efficiency for anti-oxidant activity against the catalase, superoxide dismutase, glutathione-S-transferase, glutathione reductase, glutathione peroxidase and tubulin-colchicine enzyme for anthelmintic activity. Furthermore, ADME/T profiles have been tested by ADMET SAR. The various extracts of R cana potentially inhibited the reactive oxygen species (ROS) and possessed anti-oxidant activity. In anti-oxidant assays, the IC50 values ranged from 62.08 to 440.08 μg/mL for PERC, EARC, and MERC. All the extracts demonstrated anthelmintic behaviour on P. posthuma that was dose-dependent and statistically relevant. On the other side, molecular docking analysis reveals that Gallocatechin has the best fitness score of -7.1 kcal/mol with tubulin-colchicine enzyme; Rhynchosin, Luteolin-3’,4’-dimethyl ether, Isoorientin and Orientin has the best fitness scores with different targets related to the oxidation process. In addition, all compounds were in the array of expected properties to fulfil the Lipinski law of five to be accepted as drug-like potential. The observation indicates that the R. cana possesses anti-oxidant and anthelmintic activity In vitro and In silico assays. However, further research was needed to elucidate their primary molecular mechanism of action, safety, toxicity, and bioavailability.